I (Don't) want to consume counterfeit medicines: exploratory study on the antecedents of consumer attitudes toward counterfeit medicines - Sylvester Senyo Ofori-Parku; Sung Eun Park (BMC, 2022)
Abstract Background Substandard and falsified medicine (SFM) sales (an estimated > $200 billion) has become one of the worlds' fastest growing criminal enterprises. It presents an enormous public health and safety challenge. While the developed world is not precluded from this challenge, studies focus on low-income countries. They emphasize supply chain processes, technological, and legal mechanisms, paying less attention to consumer judgment and decision-making aspects. Methods With attention to the demand side of the counterfeit medicines challenge, this survey of U.S. consumers (n = 427) sheds light on some of the social, psychological, and normative factors that underlie consumers' attitudes, risk perceptions, and purchase intentions. Results Consumers who (a) self-report that they know about the problem, (b) are older, (c) view counterfeit medicine consumption as ethical, and (d) think their significant others would approve of them using such products are more inclined to perceive lower risks and have favorable purchase intentions. Risk averseness is also inversely related to the predicted outcomes. Perceived benefit of SFMs is a factor but has no effect when risk perception and aversion, attitudes, and subjective norms are factored into the model that predicts purchase intentions. Conclusion The results of this study indicate that consumer knowledge (albeit in an unexpected direction), people's expectations about what will impress their significant others, their ethical judgments about selling and consuming counterfeits, and their risk-aversion are associated with their decision-making about counterfeit medicines. The study offers insights into a demand-side approach to addressing SFM consumption in the U.S. Implications for public health, consumer safety, and brand advocacy education are discussed.